2006
DOI: 10.1002/chem.200600914
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regioselective Rhodium‐Catalysed Hydroformylation of Unsaturated Esters: The First Practical Method for Quaternary Selective Carbonylation

Abstract: Highly regioselective hydroformylation of unsaturated esters can be achieved when a highly reactive, ligand-modified, rhodium catalyst is employed near ambient temperatures (15-50 degrees C) and pressures over 30 bar. The use of 1,3,5,7-tetramethyl-2,4,8-trioxa-6-phosphaadamantane shows distinct advantages over other commonly applied phosphanes in terms of reaction rate, and regio- and chemoselectivity. Hydroformylation of a range 1,1-di- and 1,1,2-trisubstituted unsaturated esters yields quaternary aldehydes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…However, in the 31 P{ 1 H} NMR spectra the signal appears as a singlet, due to the chemical and magnetic equivalence of both phosphorus atoms. In the 13 C{ 1 H, 31 P} NMR spectrum the signals appear as a singlet, which also verifies this model. This behaviour was also observed in symmetrically substituted bis-(phosphanyl)carbaboranes by Hill et al, who misinterpreted this as a 3 J PPЈ long-range coupling.…”
Section: Phosphorus-phosphorus Coupling In Phosphanylcarbaborane(12) supporting
confidence: 58%
See 2 more Smart Citations
“…However, in the 31 P{ 1 H} NMR spectra the signal appears as a singlet, due to the chemical and magnetic equivalence of both phosphorus atoms. In the 13 C{ 1 H, 31 P} NMR spectrum the signals appear as a singlet, which also verifies this model. This behaviour was also observed in symmetrically substituted bis-(phosphanyl)carbaboranes by Hill et al, who misinterpreted this as a 3 J PPЈ long-range coupling.…”
Section: Phosphorus-phosphorus Coupling In Phosphanylcarbaborane(12) supporting
confidence: 58%
“…The conversion was measured by 1 H NMR spectroscopy against internal standard and the spectral properties of the products were compared with authentic samples from previous work. [31] Computational Calculations: All geometry optimisations were carried out with the programme Turbomole. [35] Density-functional theory (DFT) [36] calculations employing the BP86 functional were applied for the sake of low computational costs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, although lower pressures and temperatures reduce regioselectivity, this is not as pronounced as in the case of methyl acrylate where the selectivity can be reversed. [15] There is no further gain in selectivity if pressure is increase beyond 20 bar, and for this ligand productivity is sig- Conditions: see general procedure (A). Conv.…”
Section: Resultsmentioning
confidence: 98%
“…We have recently reported that Rh catalysts derived from the monodentate phosphorus cage ligand denoted Me CgPPh show significantly enhanced reactivity, chemo-and a-selectivity in the hydroformylation of various unsaturated ester substrates, [15] The highly efficient a-selective hydroformylation reactions of a,b-unsaturated esters are only viable for the synthesis of racemic compounds since formyl esters [RCHA C H T U N G T R E N N U N G (CHO)CO 2 R')] are in an observable equilibrium with their enol form and configurationally unstable. The products from the a-selective hydroformylation of a,b-unsaturated amides are formyl amides that should exhibit less enol character due to the delocalisation between the C=O and C À N bonds and steric repulsion in the enol form.…”
Section: Introductionmentioning
confidence: 99%